Single‐phase three‐level space vector pulse width modulation algorithm for grid‐side railway traction converter and its relationship of carrier‐based pulse width modulation. Issue 3 (1st September 2014) - Song, Wensheng; Wang, Shunliang; Xiong, Chenglin; Ge, Xinglai; Feng, Xiaoyun
Abstract : A significant problem of three‐level neutral point clamped converters is the fluctuation of the neutral point voltage. A space vector pulse width modulation (SVPWM) strategy with neutral point voltage balancing for single‐phase three‐level converters adopted widely in railway traction drive system is proposed in this study. The relationship between the adopted SVPWM and carrier‐based pulse width modulation (CBPWM) with an offset voltage injection (OVI) is analysed in details. Theoretical analysis shows that the adopted SVPWM is a special type of CBPWM‐OVI methods, and can balance the neutral point voltage effectively. The high‐order harmonics of the line current distribute around twice switching frequencies while the SVPWM algorithm is adopted. These performances of the proposed SVPWM are verified by simulation and experimental tests.